Small Rice Bowl-Based Meal Plan for Energy and Marcronutrient Intake in Korean Men with Type 2 Diabetes: A Pilot Study - Ahn, Hee Jung (Korean Diabetes Association, 2011)
BACKGROUND: Koreans eat rice, which is usually served in a rice bowl. We investigated the effect of a meal plan using small rice bowls on the total energy intake (TEI) and the marcronutrient intake in Korean men with type 2 diabetes. METHODS: A total of 62 men with type 2 diabetes were divided by body mass index (BMI) (normal weight [NW], BMI<23 kg/m(2); overweight [OW], 23≤BMI<25 kg/m(2); obese [OB], BMI≥25 kg/m(2)) and proportions of carbohydrate intake to TEI (PCI) (low carbohydrate intake [LC], <55%; recommended carbohydrate intake [RC], ≥55% and ≤60%; high carbohydrate intake [HC], >60%). The 3-day dietary records were analyzed for TEI and proportions of macronutrients, before and 2 weeks after a small-sized (300 mL) rice bowl based education was given. RESULTS: There were no significant differences in the age and BMI within the sub-groups by BMI and PCI groups. In baseline, the ratio of TEI to recommended total energy intake (RTR) of OW and OB were higher than that of NW. The PCI of HC was higher than that of LC and alcohol intake of HC was lower than that of LC. After education, the reduction of RTREI in OB was higher than that in OW and NW. The reduction of PCI in HC was higher than that of LC. CONCLUSION: A small rice bowl based meal plan was effective for the reduction of energy intake and control of marcronutrient intake in Korean obese men with type 2 diabetes consuming a high carbohydrate diet.